A Miniaturized High-Gain Circular Coaxial-Fed Radiator Filtering Antenna with Configurable Radiation Nulls for Modern 5G Applications - Ravi Prakash Verma; Ashish Gupta; Bhagirath Sahu (International Journal of Antennas and Propagation)
In this paper, a low-profile, high-gain filtering antenna is proposed and developed for n-77 (3300–4200 MHz) and n-78 band (3300−3800 MHz) applications. The suggested filtering antenna is derived from a circular patch antenna. To efficiently reduce the harmonics, in the lower and upper stopbands, a pair of sectoral arcs and rectangular slots is etched out from the driven circular patch. Furthermore, the resultant structure is surrounded by a ring split at three different locations. Simulation studies reveal that this ring with three sectors is coupled with a driven patch and is highly responsible for extending the impedance bandwidth in the passband. This coupling also contributes to an extranull in the upper stopband region. In order to validate the simulated results, a prototype is fabricated, tested, and found that the measured results are consistent with the simulated one. The suggested filtering antenna, with a low profile of 0.0194λ0, demonstrates a wide fractional bandwidth of 10.2% ranging from 3.52 to 3.90 GHz, centred at 3.7 GHz. The maximum peak gain of 7.68 dB is achieved within the passband. Three configurable radiation nulls, first at 3.36 GHz, near the lower band edge; second at 4.04 GHz; and third at 4.24 GHz, near the upper band-edge frequencies, are generated to achieve fine out-of-band suppression levels.